Respuesta a la aplicación de abonos orgánicos en el cultivo de Amaranto (amaranthus caudatus l.) variedad Iniap alegría en el cantón Cotacachi, provincia de Imbabura - Castro Heredia, Hugo Bolívar (2015)
The research was conducted in Cotacachi, Imbabura province, in order to study the response to the application of five types of organic fertilizers in the cultivation of amaranth (Amaranthus caudatus L.) variety INIAP Joy. The treatments were organic fertilizers; vermicompost, cattle manure, compost, manure guinea pig, eco-Abonaza, Fertisa 10-30-10 and absolute control without application. The design of randomized complete block (RCBD) with five treatments and three replicates were used for research. The variables were evaluated: plant height at 30; 60 and 90 days after planting, days to panicle, panicle length and diameter, days to harvest, dry weight per square meter and grain yield in kg / ha. All variables applied were subjected to ANOVA using Duncan test 5%.......